DIGITALIZATION OF LEADERSHIP COMMUNICATION, WORK MOTIVATION, AND NURSE PERFORMANCE: A LITERATURE REVIEW - Wardana, Dewa Gede Wisnu; Agustin, Ni Luh Putu Inca Buntari; Negara, I Gusti Ngurah Made Kusuma; Yusniawati, Yustina ni putu (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Digitalization is a process of transformation from a traditional era to a digital era influenced by technological developments. Digitization affects various aspects of life, including the health sector, especially leadership communication which influences work motivation and nurse performance which is visible during the Covid-19 pandemic. The purpose of this literature review is to identify digitalization in leadership communication, work motivation, and performance of nurses or employees. Design: This research design is a literature review. Data Sources: Search for articles using four journal databases, namely OWL (Online Wiley Library), Google Scholar, Pubmed, and Science Direct. Review Methods: Used PRISMA Flow Diagram to find a total of 11 articles that met the inclusion criteria were reviewed. Results and conclusion: The results of the review of the article entitled "Digitalization of Leadership Communication, Work Motivation, and Nurse Performance" found that the digitalization process in leadership communication is fairly difficult. Leaders must be able to use various types of digital communication media in communicating with staff or nurses. When leading transformational digital change, leaders strive for constant communication and coaching-oriented actions. Leaders who can be able to transform well in digitalization will be able to provide good work motivation for staff or nurses. Effective work motivation in the digitalization of leader communication will impact good nurse performance as shown by nurses coming on time, providing fast service, adhering to standards, and making a solid team